It is currently 18 Dec 2017, 06:56

# Final Week of R1 Decisions:

CHAT Rooms | MIT Sloan | McCombs

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Function

Author Message
Manager
Joined: 12 Feb 2008
Posts: 177

Kudos [?]: 47 [0], given: 0

### Show Tags

23 Sep 2008, 06:10
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Function $$f(x)$$ satisfies $$f(x) = f(x^2)$$ for all $$x$$ . Which of the following must be true?

* $$f(4) = f(2)f(2)$$
* $$f(16) - f(-2) = 0$$
* $$f(-2) + f(4) = 0$$
* $$f(3) = 3f(3)$$
* $$f(0) = 0$$

Kudos [?]: 47 [0], given: 0

Current Student
Joined: 28 Dec 2004
Posts: 3345

Kudos [?]: 325 [0], given: 2

Location: New York City
Schools: Wharton'11 HBS'12

### Show Tags

23 Sep 2008, 06:21
if f(x)=f(x^2) then f(-2)=f(4)...if f(4) then assume if x=4 then f(4)=f(4^2) i.e f(16)..

I will go with B..

Kudos [?]: 325 [0], given: 2

Manager
Joined: 22 Jul 2008
Posts: 146

Kudos [?]: 22 [0], given: 0

### Show Tags

23 Sep 2008, 07:13
f(-2) = f(4) = f(16)
Hence, f(-2) = f(16)
f(16) - f(-2) = 0
Ans. is B

Kudos [?]: 22 [0], given: 0

Manager
Joined: 12 Feb 2008
Posts: 177

Kudos [?]: 47 [0], given: 0

### Show Tags

24 Sep 2008, 04:28
KASSALMD wrote:
f(-2) = f(4) = f(16)
Hence, f(-2) = f(16)
f(16) - f(-2) = 0
Ans. is B

Why do you square twice.

f(-2)=f(4) and thats it.
where does f(16) come from. i understand that f(4)=f(16) but the question says only that f(x)=f(x^2)...........

Kudos [?]: 47 [0], given: 0

SVP
Joined: 17 Jun 2008
Posts: 1530

Kudos [?]: 282 [0], given: 0

### Show Tags

25 Sep 2008, 11:41
elmagnifico wrote:
KASSALMD wrote:
f(-2) = f(4) = f(16)
Hence, f(-2) = f(16)
f(16) - f(-2) = 0
Ans. is B

Why do you square twice.

f(-2)=f(4) and thats it.
where does f(16) come from. i understand that f(4)=f(16) but the question says only that f(x)=f(x^2)...........

What f(x) = f(x^2) means that f(2) = f(4) = f(16) = f(256) = ........

Hence, one can use f(16) in place of f(4).

Kudos [?]: 282 [0], given: 0

Re: Function   [#permalink] 25 Sep 2008, 11:41
Display posts from previous: Sort by

# Function

Moderator: chetan2u

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.